COMPARATIVE ANALYSIS OF MORPHOLOGICAL STRUCTURES IN INDO-EUROPEAN LANGUAGES - Gulmira Usmonova,; Madina Abjaparova,; Ruxshona Valiyeva, (TADQIQOTLAR, 2025)
Abstract This study presents a comparative analysis of morphological structures within selected Indo-European languages, focusing on the typological diversity and historical development  of  inflectional  and  derivational  morphology.  The  Indo-European language family, which includes English, Sanskrit, Greek, Latin, Russian, and others, demonstrates  both  shared  grammatical  roots  and  unique  evolutionary  paths.  By analyzing morphological features such as case marking, verb conjugation, and nominal declension, this research identifies patterns of retention, innovation, and simplification across  branches.  Special  attention  is  given  to  how  morphological  systems  reflect broader  syntactic  and  phonological  changes  over  time.  The  study  employs  a comparative-historical method, drawing on linguistic data from classical and modern sources to examine both fusional and analytical tendencies within the family. Results show that morphological complexity correlates with historical linguistic change and language  contact,  influencing  how  modern  Indo-European  languages  express grammatical  relations.  This  analysis  contributes  to  understanding  the  evolution  of morphological typology and the mechanisms of linguistic diversification.